Pelestarian Warisan Budaya Kampung Tradisional Bela Ragi Berbasis Pemeberdayaan Masyrakat. - Ngiso, Vinsensia Quirina Ngene; Wardi, I Nyoman; Bawono, Rochtri Agung (Peneliti.net, 2025)
Cultural heritage is a legacy from a particular community that has important value because it can show the level of civilization. This study discusses the preservation strategy of the Cultural Heritage of the Bela Ragi Traditional Village based on community empowerment. To answer this problem, a preservation strategy needs to be formulated based on research. The author conducted research by collecting data through observation, interviews, and literature studies. The analysis was then carried out using the SWOT analysis method. The results of the analysis show that the preservation of Cultural Heritage can be improved with a preservation strategy through community empowerment. The strategies that can be taken are by empowering the government apparatus, namely the Ngada Regency Education Office, and strengthening the Bela Ragi community organization structure. Both strategies are interrelated and inseparable from each other. The direction of preservation must be strengthened with three programs, namely the development of government human resources, the development of community organization programs, and the development of infrastructure and facilities. The activities will be successful if carried out in an integrated and sustainable manner. Keywords: Preservation strategy, Cultural heritage, SWOT analysis